Sensory evaluation of provitamin A carotenoid-rich banana cultivars on trial for potential adoption in Burundi and Eastern Democratic Republic of Congo - Ekesa, B.; Nabuuma, D.; Kennedy, G.; Bergh, Inge van den (International Society for Horticultural Science, 2017)
Introduction – Vitamin A deficiency (VAD) is a widespread health problem in Eastern Africa where banana is a staple food crop. Research has shown that certain banana cultivars grown outside Eastern Africa are rich in provitamin A carotenoids (pVACs) and could thus be utilized in addressing VAD in the region. The objective of this research was to compare the consumer preference of the pVAC-rich banana cultivars with that of local cultivars of the same genome and following similar postharvest handling treatments. Materials and methods – Evaluation trials of selected pVAC-rich banana cultivars [‘Apantu’ (AAB, Plantain), ‘Bira’ (AAB, Iholena), ‘Lahi’ (AAB, Popo’ulo), ‘Pelipita’ (ABB), ‘Sepi’ (AA), ‘To’o’ (AA), ‘Hung Tu’ (AA) and ‘Laï’ (AAA)] were established in Burundi and Eastern Democratic Republic of Congo (DRC). During sensory evaluations 450 panellists (50% male and 50% female) tested the products using standard procedures and rated them on a 5-point hedonic scale. Dessert types were served raw; cooking types were boiled, roasted and pan-fried. The attributes evaluated included: peel appearance, ease of peeling, pulp appearance, aroma, texture in hand, texture in mouth, taste and overall acceptability. Results and discussion – In Burundi, all the cultivars had overall acceptability median scores of 4 (good). In North Kivu, DRC, the overall acceptability medians ranged from fair to very good (3-5). In South Kivu, DRC, the median overall acceptability scores were good (4) for all cultivars except ‘To’o’ and ‘Gros Michel’ (AAA) that scored 3 and 5 respectively (fair and very good). In all three sites and for all the cultivars, there was a significant correlation between the scores for texture in the mouth, taste and the scores for overall acceptability. Conclusion – Taste and texture in mouth have proved to be major consumption attributes that determine acceptability of a banana cultivar. A number of the pVAC-rich cultivars have shown good potential for adoption within existing farming systems and diets in these regions.